2007
DOI: 10.1111/j.1442-2018.2007.00311.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the health‐promoting lifestyle, enrollment level, and academic performance of College of Nursing students in Kuwait

Abstract: This descriptive study of 224 nursing students assessed their health-promoting lifestyle profile and correlated it with the levels of enrollment in nursing courses and academic performance. The health-promoting lifestyle profile was measured by Walker's Health-promoting Lifestyle Profile II instrument. Academic performance was measured by assessing the nursing grade point average and general grade point average of the students. The students had positive health-promoting lifestyles with significant differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
65
2
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 20 publications
12
65
2
11
Order By: Relevance
“…"I consume and save electricity and water considering the limited resources" 39.5% 59.6% 9,10 In our study, the HLSB-II scale average points were higher than previous studies on university students; however, the results represent only a medium level of healthy lifestyle behavior, highlighting the need for further education in this area. The higher results of the students may be related to the high sociocultural level of the students and the interest of them, because this was an elective course.…”
Section: The Propositions Pretest Posttestcontrasting
confidence: 55%
“…"I consume and save electricity and water considering the limited resources" 39.5% 59.6% 9,10 In our study, the HLSB-II scale average points were higher than previous studies on university students; however, the results represent only a medium level of healthy lifestyle behavior, highlighting the need for further education in this area. The higher results of the students may be related to the high sociocultural level of the students and the interest of them, because this was an elective course.…”
Section: The Propositions Pretest Posttestcontrasting
confidence: 55%
“…Studies in Finland (children) and elsewhere (adolescents) reported a positive association between PA and academic achievement (12,13). In contrast, in Kuwait, there was no direct association between PA and academic achievement (14); and in the UK, there was no direct association between PA and students' academic achievement whether the indicator employed was subjective (self reported) or objective (actual module grade) (15).…”
Section: Introductionmentioning
confidence: 78%
“…If they were convinced of the need to adopt a healthy lifestyle, with adequate physical exercise and a proper diet, the task of encouraging their patients to do likewise would be much easier. As indicated by McDowell and Al-Kandari [38] [39], activity promotion and personal behaviour of health care professionals are associated with the promotion of healthcare for patients. Hence, with their health-promoting lifestyle and knowledge, student nurses would be able to perform their role more effectively as practitioners.…”
Section: Discussionmentioning
confidence: 99%